Translation of selected passage from the prose anthology Ren Jian Qing Xing ( 《人间清醒》) by contemporary Chinese writer Liang Xiaosheng - Chen, Lijun (Nanyang Technological University, 2024)
This capstone project delves into the intricate landscape of translation strategies as applied to contemporary Chinese prose, with a specific focus on the nuanced interplay between domestication, foreignization, and "Reader Response" Theory. Through a meticulous analysis of practical translation examples, this study elucidates the multifaceted decisions and challenges encountered by translators when bridging linguistic and cultural divides.